(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2024)
This cross-sectional study investigated the association of SNPs rs670 (C>T) and rs693 (G>A) with parameters of lipid metabolism and endothelial activation in 167 subjects, including 86 COVID-19 outpatients and 81 healthy subjects (control group) matched for sex and age. Serum levels of total cholesterol (TC), high-density lipoprotein cholesterol (HDL-c), low-density lipoprotein cholesterol (LDL-c), non-high-density lipoprotein cholesterol (non-HDL-c), triglycerides (TG), apolipoproteins (Apo A-I and B), and vascular cell adhesion molecule-1 (VCAM-1) were determined. The SNPs were genotyped by quantitative polymerase chain reaction (qPCR). A p -value<0.05 was assumed. COVID-19 outpatients showed increases in TC (187.0±48.3 vs . 160.8±32.0 mg/dL), LDL-c (110.3±41.5 vs . 98.8±28.2 mg/dL), non-HDL-c (138.3±45.8 vs . 115.6±31.6 mg/dL), TG (139.7±80.3 vs . 84.9±35.1 mg/dL), and Apo A-I (149.5±40.0 vs . 133.3±20.9 mg/dL), along with a high frequency of hypercholesterolemia and hypertriglyceridemia. VCAM-1 levels were double those of the control (682.7±231.8 vs. 299.3±102.9 ng/mL) and a strong predictor of COVID-19 (AUC=0.946). Moreover, VCAM-1 correlated with TC (r = -0.223) and HDL-c (r = -0.225). The decrease in TG and VCAM-1 is predicted by the dominance of the T allele (rs670) and its codominance with the A (rs693) allele in COVID-19 outpatients. COVID-19 has been shown to be associated with dyslipidemias and endothelial activation, and apolipoprotein polymorphisms may influence this.